Cytotoxic Test of Cassia alata L. Leaves Ethanol Extracts, Fractions, and Main Compounds against MCF-7 Cells - Khoerunisah, Marya Salfia; Angelina, Marissa; Kasiyati, Kasiyati (Indonesian Journal of Cancer Chemoprevention, 2022)
Cancer is the primary cause of death worldwide. Conventional cancer treatment is known to be less than optimal because of its chemoresistance and toxicity to normal cells. The search for cancer drugs from natural ingredients is still being carried out as an effort to overcome these problems. Cassia alata L. leaf extract is known to have antibacterial and antitumor activities. The main compounds of C. alata L. leaves (emodin, aloe-emodin, and kaempferol) have been reported to have antiproliferative activity. This study aimed to examine the cytotoxic activity of the C. alata L. leaves ethanol extracts, fractions, and main compounds against breast cancer cells (MCF-7). Cytotoxic activity was carried out by the MTT method. IC50 was determined by linear regression analysis describing the relationship between concentration and % cell viability. The results showed that aloe-emodin, emodin, and kaempferol had better cytotoxic activity than the extract and fractions of the C. alata L. leaves with IC50 values respectively 12.7 ppm, 18.1 ppm, and 131.3 ppm.Keywords: Breast cancer, cytotoxic assay, Cassia alata L., ketepeng cina, MCF-7.